Pengaruh Kemandirian Fiskal, Belanja Operasi Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Indonesia - Rina Chrisnawati; Etik Umiyati; Rosmeli (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study aims to analyze the development and the influence of fiscal independence ratio, operating expenditure ratio, and labor force on economic growth in 34 provinces in Indonesia during the period 2020–2024. The analysis method employed is panel data regression using the Fixed Effects Model (FEM) approach, following the results of the Chow test and Hausman test. The results show that the fiscal independence ratio has a positive and significant effect on economic growth. The operating expenditure ratio also has a positive and significant effect on economic growth. Meanwhile, the labor force variable has a negative but insignificant effect on economic growth. The Adjusted R-Square value of 0.6890 indicates that the three independent variables together can explain 68.90 percent of the variation in economic growth. Descriptively, the 2020–2024 period was marked by economic contraction due to the Covid-19 pandemic in 2020, followed by strong recovery in 2021–2022 and stabilization in 2023–2024. There is a clear disparity between regions, where Java Island dominates fiscal independence and labor absorption, while eastern Indonesia shows high economic growth driven by the mining sector but still has low fiscal independence.